Field measurements of trace gases and aerosols emitted by peat fires in Central Kalimantan, Indonesia, during the 2015 El Niño - C. E. Stockwell; C. E. Stockwell; T. Jayarathne; M. A. Cochrane; K. C. Ryan; K. C. Ryan; E. I. Putra; E. I. Putra; B. H. Saharjo; A. D. Nurhayati; I. Albar; D. R. Blake; et al. (Atmospheric Chemistry and Physics, 2016)
Peat fires in Southeast Asia have become a major annual source of trace gases and particles to the regional–global atmosphere. The assessment of their influence on atmospheric chemistry, climate, air quality, and health has been uncertain partly due to a lack of field measurements of the smoke characteristics. During the strong 2015 El Niño event we deployed a mobile smoke sampling team in the Indonesian province of Central Kalimantan on the island of Borneo and made the first, or rare, field measurements of trace gases, aerosol optical properties, and aerosol mass emissions for authentic peat fires burning at various depths in different peat types. This paper reports the trace gas and aerosol measurements obtained by Fourier transform infrared spectroscopy, whole air sampling, photoacoustic extinctiometers (405 and 870 nm), and a small subset of the data from analyses of particulate filters. The trace gas measurements provide emission factors (EFs; grams of a compound per kilogram biomass burned) for up to  ∼  90 gases, including CO2, CO, CH4, non-methane hydrocarbons up to C10, 15 oxygenated organic compounds, NH3, HCN, NOx, OCS, HCl, etc. The modified combustion efficiency (MCE) of the smoke sources ranged from 0.693 to 0.835 with an average of 0.772 ± 0.053 (n  =  35), indicating essentially pure smoldering combustion, and the emissions were not initially strongly lofted. The major trace gas emissions by mass (EF as g kg−1) were carbon dioxide (1564 ± 77), carbon monoxide (291 ± 49), methane (9.51 ± 4.74), hydrogen cyanide (5.75 ± 1.60), acetic acid (3.89 ± 1.65), ammonia (2.86 ± 1.00), methanol (2.14 ± 1.22), ethane (1.52 ± 0.66), dihydrogen (1.22 ± 1.01), propylene (1.07 ± 0.53), propane (0.989 ± 0.644), ethylene (0.961 ± 0.528), benzene (0.954 ± 0.394), formaldehyde (0.867 ± 0.479), hydroxyacetone (0.860 ± 0.433), furan (0.772 ± 0.035), acetaldehyde (0.697 ± 0.460), and acetone (0.691 ± 0.356). These field data support significant revision of the EFs for CO2 (−8 %), CH4 (−55 %), NH3 (−86 %), CO (+39 %), and other gases compared with widely used recommendations for tropical peat fires based on a lab study of a single sample published in 2003. BTEX compounds (benzene, toluene, ethylbenzene, xylenes) are important air toxics and aerosol precursors and were emitted in total at 1.5 ± 0.6 g kg−1. Formaldehyde is probably the air toxic gas most likely to cause local exposures that exceed recommended levels. The field results from Kalimantan were in reasonable agreement with recent lab measurements of smoldering Kalimantan peat for “overlap species,” lending importance to the lab finding that burning peat produces large emissions of acetamide, acrolein, methylglyoxal, etc., which were not measurable in the field with the deployed equipment and implying value in continued similar efforts. The aerosol optical data measured include EFs for the scattering and absorption coefficients (EF Bscat and EF Babs, m2 kg−1 fuel burned) and the single scattering albedo (SSA) at 870 and 405 nm, as well as the absorption Ångström exponents (AAE). By coupling the absorption and co-located trace gas and filter data we estimated black carbon (BC) EFs (g kg−1) and the mass absorption coefficient (MAC, m2 g−1) for the bulk organic carbon (OC) due to brown carbon (BrC). Consistent with the minimal flaming, the emissions of BC were negligible (0.0055 ± 0.0016 g kg−1). Aerosol absorption at 405 nm was  ∼  52 times larger than at 870 nm and BrC contributed ∼  96 % of the absorption at 405 nm. Average AAE was 4.97 ± 0.65 (range, 4.29–6.23). The average SSA at 405 nm (0.974 ± 0.016) was marginally lower than the average SSA at 870 nm (0.998 ± 0.001). These data facilitate modeling climate-relevant aerosol optical properties across much of the UV/visible spectrum and the high AAE and lower SSA at 405 nm demonstrate the dominance of absorption by the organic aerosol. Comparing the Babs at 405 nm to the simultaneously measured OC mass on filters suggests a low MAC ( ∼  0.1) for the bulk OC, as expected for the low BC/OC ratio in the aerosol. The importance of pyrolysis (at lower MCE), as opposed to glowing (at higher MCE), in producing BrC is seen in the increase of AAE with lower MCE (r2 =  0.65).